1991
DOI: 10.4319/lo.1991.36.2.0268
|View full text |Cite
|
Sign up to set email alerts
|

Weak coupling of bacterial and algal production in a heterotrophic ecosystem: The Hudson River estuary

Abstract: Bacterial abundances, biomass, and production were measured over a 3-yr period at stations along a 15%km reach of the tidal, freshwater Hudson River. Bacterial abundances ranged from 1 to 10 x 1 O6 cells ml-' with maximal values in summer. Abundance and production averaged over all stations for the ice-free season (April through December) were 4.9 and 9.1 x lo9 cells liter-l dm', respectively, and both were significantly correlated with temperature. Neither bacterial abundance nor production showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
165
1
12

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(204 citation statements)
references
References 30 publications
26
165
1
12
Order By: Relevance
“…Coastal waters and especially estuaries are heterotrophic systems and mostly characterized by a larger gross respiration rate than primary production (Vadstein and Olsen 1989). Indeed, recent investigations in the estuary of the Delaware (Coffin and Sharp 1987), the St. Lawrence (Painchaud and Therriault 1989), and in the Hudson River (Findlay et al 1991) demonstrated that the algae-bacteria link is not statistically detectable when additional C sources are available for mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal waters and especially estuaries are heterotrophic systems and mostly characterized by a larger gross respiration rate than primary production (Vadstein and Olsen 1989). Indeed, recent investigations in the estuary of the Delaware (Coffin and Sharp 1987), the St. Lawrence (Painchaud and Therriault 1989), and in the Hudson River (Findlay et al 1991) demonstrated that the algae-bacteria link is not statistically detectable when additional C sources are available for mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…The overwhelming majority of studies concerning freshwater microbial food webs have been conducted in lentic environments with comparatively little research focused on heterotrophic bacteria and protozoa in temperate rivers (Edwards & Meyer 1986, Carlough & Meyer 1990, Dolan & Gallegos 1991, Findlay et al 1991. The microbial food web could be particularly important to carbon and nutrient dynamics in rivers due to the often high loadings of allochthonous organic matter (Edwards & Meyer 1986, Findlay et al 1991, Sabater et al 1993, and low zooplankton abundances (Pace et al 1992, Basu & Pick 1996.…”
Section: Introductionmentioning
confidence: 99%
“…These webs can be visualized as 'microbial loops', in which heterotrophic bacteria convert dissolved organic matter of autochthonous or allochthonous origin into particulate organic carbon (Azam et al 1983, Berninger et al 1991, Findlay et al 1991). The heterotrophic bacteria are then grazed by heterotrophic flagellates and small ciliates (Porter et al 1985, Berninger et al 1991) which, in turn, may be consumed by larger ciliates, microzooplankton and cladocerans (Gasol & Vaqu6 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In Cabo Frio, the infl uence from the SACW resulted in the lower temperatures and higher N-NO 3 levels observed. In both areas the high DOM C:N ratios indicate the predominance of allochthonous DOM sources, rich in organic carbon (Findlay et al 1991). In Cabo Frio, despite the apparent lower infl uence of terrestrial inputs, DOM C:N was unexpectedly higher, which suggests smaller phytoplankton contribution to the DOM pool in comparison to Guanabara Bay, probably due to lower PP rates (Baines & Pace 1991).…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, when DOC sources are mostly allochthonous, there is no coupling between those plankton compartments and BP may exceed PP (e.g. Findlay et al 1991).…”
Section: Introductionmentioning
confidence: 99%